2018
DOI: 10.1371/journal.pone.0200242
|View full text |Cite|
|
Sign up to set email alerts
|

Adoption of routine virologic testing and predictors of virologic failure among HIV-infected children on antiretroviral treatment in western Kenya

Abstract: BackgroundAccess to routine virologic monitoring, critical to ensuring treatment success, remains limited in low- and middle-income countries. We report on implementation of routine viral load (VL) monitoring and risk factors for virologic failure among HIV-infected children on antiretroviral treatment (ART) in Western Kenya.MethodsRoutine VL testing was introduced in western Kenya in November 2013. We performed a case-control study among 1190 HIV-infected children ≤15 years on ART who underwent routine VL tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 28 publications
13
36
1
Order By: Relevance
“…Fourth, risk factors for virologic failure in both cohorts were advanced HIV-related disease and/or immunosuppression. These findings are in line with previous reports [ 29 , 30 , 31 ], although associations between advanced HIV disease and virologic failure are not always consistent [ 32 , 33 ]. Being married or widowed offered protection in the 12-month cohort against virologic failure and this is possibly due to the supportive efforts of spouses/families in ensuring adherence to treatment and compliance with follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Fourth, risk factors for virologic failure in both cohorts were advanced HIV-related disease and/or immunosuppression. These findings are in line with previous reports [ 29 , 30 , 31 ], although associations between advanced HIV disease and virologic failure are not always consistent [ 32 , 33 ]. Being married or widowed offered protection in the 12-month cohort against virologic failure and this is possibly due to the supportive efforts of spouses/families in ensuring adherence to treatment and compliance with follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…This study also revealed opportunistic infections during follow-up were strongly associated with the occurrence of virological failure. This result is concordant with other reports from Tanzania (19) and Kenya (25), which demonstrated that co-morbidities such as TB (one of the opportunistic infections) were associated with the occurrence of virological failure. This is well-known that co-morbidities such as TB weaken the immune system among patients and rapidly increase HIV disease progression to its advanced stage.…”
Section: Discussionsupporting
confidence: 92%
“…Kenya (25), which demonstrated that co-morbidities such as TB (one of the opportunistic infections) were associated with the occurrence of virological failure. This is well-known that co-morbidities such as TB weaken the immune system among patients and rapidly increase HIV disease progression to its advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…From the studies conducted in Nigeria and Cambodia risk factors for ART treatment failure were ARV exposure and sever immunosuppression before start of ART [26]. From a study conducted in Kenya, the factors were base line CD4 below 50 cells [29]. From these studies, the risk factors including low base line CD4 and poor adherence were found to be significant associated factors for ART treatment failure.…”
Section: Discussionmentioning
confidence: 99%